Cardiolipin is required for membrane docking of mitochondrial ribosomes and protein synthesis - Lee, R.G.; Gao, J.; Siira, S.J.; Shearwood, A.M.; Ermer, J.A.; Hofferek, V.; Mathews, J.C.; Zheng, M.; Reid, G.E.; Rackham, Oliver; Filipovska, Aleksandra (COMPANY BIOLOGISTS LTD, 2020)
The mitochondrial inner membrane contains a unique phospholipid known as cardiolipin (CL), which stabilises the protein complexes embedded in the membrane and supports its overall structure. Recent evidence indicates that the mitochondrial ribosome may associate with the inner membrane to facilitate co-translational insertion of the hydrophobic oxidative phosphorylation (OXPHOS) proteins into the inner membrane. We generated three mutant knockout cell lines for the CL biosynthesis gene Crls1 to investigate the effects of CL loss on mitochondrial protein synthesis. Reduced CL levels caused altered mitochondrial morphology and transcriptome-wide changes that were accompanied by uncoordinated mitochondrial translation rates and impaired respiratory chain supercomplex formation. Aberrant protein synthesis was caused by impaired formation and distribution of mitochondrial ribosomes. Reduction or loss of CL resulted in divergent mitochondrial and endoplasmic reticulum stress responses. We show that CL is required to stabilise the interaction of the mitochondrial ribosome with the membrane via its association with OXA1 (also known as OXA1L) during active translation. This interaction facilitates insertion of newly synthesised mitochondrial proteins into the inner membrane and stabilises the respiratory supercomplexes.